PEMANFAATAN PUPUK ORGANIK LIMBAH BUDIDAYA BELIMBING TASIKMADU TUBAN TERHADAP PERTUMBUHAN DAN HASIL PRODUKSI TANAMAN PAKCOY (Brassica rapa L.) - Heldy Gunawan; Mutiara Dewi Puspitawati; Inanpi Hidayati Sumiasih (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2019)
The cultivation of carambola produced some waste that can be used as organic fertilizer. Organic fertilizer is useful to improve soil conditions and enrich the nutrient content contained therein so that it is easily absorbed by cultivated plants such as pakcoy (Brassica rapa L.). The optimum pakcoy production is supported by good land management in order to meet the availability of nutrients needed by the addition of inorganic fertilizers and starfruit organic fertilizer. The study was conducted at Attaqie Farm, Tuban in November 2018 to May 2019. The experimental design used was randomized completely block design with two factors carambla derivated organic fertilizer 10 tons ha-1 , 20 tons ha-1, 30 tons ha-1 and inorganic fertilizer  0 kg ha-1; 50 kg ha-1; 100 kg ha-1. The results showed that carambola derivated organic fertilizer contained N, P, K, S, Ca, and Mg about 6.19%,  0.94%, 75.04%,  0.02%,  20.13%, and 47.23%, respectively. The dosage of 50% inorganic fertilizer and 10 tons of carambola organic fertilizer gave optimum results for the growth of plant height, number of leaves, leaf width, stem diameter, canopy weight, root length and root weight of pakcoy plants. Fertilization using a dose of organic fertilizer 10 tons ha-1 could reduce 50% of the need of inorganic fertilizer.Keywords: fertilizer efficiency, organic fertilizer, pakcoy, starfruit waste, verticulture